A neutral branched platinum–acetylide complex possessing a tetraphenylethylene core: preparation of a luminescent organometallic gelator and its unexpected spectroscopic behaviour during sol-to-gel transition. Issue 82 (1st September 2015) - Ren, Yuan-Yuan; Wu, Nai-Wei; Huang, Junhai; Xu, Zheng; Sun, Dan-Dan; Wang, Cui-Hong; Xu, Lin
Abstract : A neutral branched platinum–acetylide complexTPA possessing a tetraphenylethylene core was successfully prepared, which was found to form luminescent organometallic gels in ethyl acetate. Abstract : A neutral branched platinum–acetylide complex TPA possessing a tetraphenylethylene core was successfully prepared, which was found to form luminescent organometallic gels in ethyl acetate. Stimulated by temperature or F −, the reversible gel–sol transition was realized. More interestingly, TPA exhibited an unexpected blue shift of the emission during the sol-to-gel transition.